2015
DOI: 10.2166/washdev.2015.014
|View full text |Cite
|
Sign up to set email alerts
|

Faecal sludge simulants to aid the development of desludging technologies

Abstract: This paper presents a review of currently available data from the literature on the undrained shear strength, bulk density, stickiness and debris content of faecal sludge. Those data have been used to develop two different simulants that replicate the full range of shear strengths and densities reported for faecal sludge. Comprehensive specifications are also presented for the debris or solid waste found in latrines to more closely replicate the challenge of pumping faecal sludge. Finally, a design guide has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…It should be noted that these values, at around 6 kPa, are substantially greater than the sludge strengths reported in previous work, yet only in 21 of the 439 pits tested did the penetrometer sink to the base of the pit with no blows. This indicates that in any pit latrine for which dynamic cone penetrometer testing has been carried out and a blow-count reported, the sludge strength must exceed 6 kPa and hence be greater than the upper limit of 2 kPa previously proposed by Radford et al (2015).…”
Section: Application To Field Datamentioning
confidence: 73%
See 2 more Smart Citations
“…It should be noted that these values, at around 6 kPa, are substantially greater than the sludge strengths reported in previous work, yet only in 21 of the 439 pits tested did the penetrometer sink to the base of the pit with no blows. This indicates that in any pit latrine for which dynamic cone penetrometer testing has been carried out and a blow-count reported, the sludge strength must exceed 6 kPa and hence be greater than the upper limit of 2 kPa previously proposed by Radford et al (2015).…”
Section: Application To Field Datamentioning
confidence: 73%
“…Despite this, faecal sludge with strengths exceeding the 'portable' penetrometer's maximum reading was found in 7 of the 30 pits. While 87% of the tested pits contained some 'weak sludge of comparable strength to that previously reported' , 60% of them were also found to contain sludge which was stronger than 400 Pa. Radford et al (2015) collected existing data on the shear strength and bulk density of faecal sludge. The highest undrained shear strength directly measured was 2 kPa, but rheological data which was extrapolated from weaker samples in Woolley et al (2014a, b) suggested that the maximum shear strength of faecal sludge could be 10 kPa, for sludge with total solids contents of up to 40%.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In this study, we used 0% bentonite to simulate septic tank wastewater, 3-7% bentonite to simulate thin sludge found in wet pit latrines, and 9-12% bentonite to simulate thick fecal sludge in wet and dry pit latrines. The model pit latrine also contained a standard trash formulation 20 and contained items such as but not limited to plastic bags, condoms, magazines, and sanitary napkins (Table 1).…”
Section: Simulated Pit Latrinesmentioning
confidence: 99%
“…While the disposal of solid waste into pit latrines and other sanitation systems is detrimental to transport and treatment of the faecal sludge, and is therefore discouraged, it frequently happens nonetheless. The reasons for this vary, but the lack of alternative solid waste disposal options and the stigma surrounding menstrual hygiene are two common examples (Radford et al, 2015; Tembo et al, 2017). A flush should not necessarily accommodate this behaviour, but it is likely that menstrual absorbents are disposed regardless of user instruction.…”
Section: Introductionmentioning
confidence: 99%